2012
DOI: 10.1093/eurpub/cks059
|View full text |Cite
|
Sign up to set email alerts
|

Small-area analysis of social inequalities in residential exposure to road traffic noise in Marseilles, France

Abstract: Finding the highest noise exposure in midlevel deprivation areas was unexpected, given the general literature on environmental inequalities. It highlights the need to study the diversity of the patterns of environmental inequalities across various economic, social and cultural contexts. Comparative studies of environmental inequalities are needed, between regions and countries, for noise and other pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The boxplot shows a small tendency for a U-shape for the connection of L den and income, which was related to the attractive city center locations in Hamburg. A similar, yet stronger U-connection was discovered for Marseille [37] and Amsterdam [93], showing the importance of context variables for the interpretation of results [36].…”
Section: Discussion Conclusion and Outlooksupporting
confidence: 70%
“…The boxplot shows a small tendency for a U-shape for the connection of L den and income, which was related to the attractive city center locations in Hamburg. A similar, yet stronger U-connection was discovered for Marseille [37] and Amsterdam [93], showing the importance of context variables for the interpretation of results [36].…”
Section: Discussion Conclusion and Outlooksupporting
confidence: 70%
“…To close, we did not consider the causal effects of urban dynamics and planning policies and processes on environmental distributive and procedural environmental justice in our analysis. In addition, our study results have to be re-examined and reflected by future studies from different planning contexts (see also Bocquier et al 2012).…”
Section: Journal Of Environmental Planning and Management 1415mentioning
confidence: 86%
“…Forkenbrock and Schweitzer 1999;Mielck 2004;Kohlhuber et al 2006), whereas another study demonstrated the opposite pattern (Harvard et al 2011). A recent study revealed highest noise exposures for those subgroups who are socially 'in-between' (Bocquier et al 2012). However, scaling of research and study design (ecological, individual or multilevel), exposure classification and data resolution may veil (or unveil) socio-spatial differences (Lakes and Br€ uckner 2011) and partially account for the mixed evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations